Seroprevalence of scrub typhus, murine typhus and spotted fever groups in North Korean refugees - Jihye Um; Yeonghwa Nam; Ji Na Lim; Misuk Kim; Yeonsu An; Se Hee Hwang; Jun-Sun Park (International Journal of Infectious Diseases, 2021)
Objectives: The aim of this study was to investigate the seroprevalence of antibodies against scrub typhus, murine typhus and spotted fever groups among North Korean refugees within 1 year of their arrival in South Korea. Methods: We recruited North Korean refugees who had settled in South Korea after a short stay in a third country and did not have any health problems. The antibody titer was measured using a commercial indirect fluorescence assay immunoglobulin G antibody kit. Results: The seroprevalence of antibodies against scrub typhus, murine typhus, and spotted fever groups among the 99 participants was 22.2%, 17.2%, and 10.1%, respectively, with 8.1% of participants testing positive for both spotted fever and murine typhus. Conclusions: Refugees may be exposed to rickettsial infections in North Korea and their journey from North Korea. This study is the first to report the seroprevalence of antibodies against the 3 common rickettsial diseases among North Korean refugees. The findings suggest that rickettsial infections should be added to the list of differential diagnoses for North Koreans with fever after entering South Korea.